The emergence of hyperendemic dengue in Bangladesh: An ecological study of structural breaks and transmission regime shifts, 2008–2025 - Pratyay Hasan; Tazdin Delwar Khan; Mohd. Arifuzzaman; Md. Saiful Islam; Mohammad Emdadul Haque (PLoS ONE, 2026)
Background Dengue fever in Bangladesh has escalated from sporadic outbreaks to a persistent, nationwide health crisis. Traditional epidemiological analyses often assume a constant transmission regime, potentially overlooking fundamental shifts driven by viral, environmental, or societal factors. This population-level ecological time-series observational study aimed to identify and characterize significant structural breaks in the time series of dengue admissions in Bangladesh to define distinct epidemiological phases. Methods Monthly dengue hospital admission data (January 2008 ─ October 2025) were obtained from the Institute of Epidemiology, Disease Control and Research (IEDCR) and Directorate General of Health Services (DGHS) public archives. Analyses included STL seasonal-trend decomposition, the Zivot-Andrews unit root test (primary break detection), multi-algorithm breakpoint detection (PELT, Binary Segmentation, Window-based), K-means clustering (optimal at 3 clusters, silhouette score 0.867), and Markov regime-switching models. Findings Ten structural breaks were identified through a consensus ranking approach. The most prominent break occurred in May 2021 (consensus score = 3). The Markov regime-switching model delineated three distinct transmission regimes: 1) a Low Baseline Regime (2008 ─ 2023) with a mean of 47 monthly cases (95% CI: 36 ─ 57); 2) an Intermediate Regime (2008 ─ 2025) with a mean of 1,288 monthly cases (95% CI: 927 ─ 1,648); and 3) a Hyperendemic Regime (2019 ─ 2025) with a mean of 26,127 monthly cases (95% CI: 17,207─35,048), representing a 556-fold increase over the low baseline. Seasonality strength was moderate (0.335), but the peak-to-trough seasonal ratio approached 180, indicating pronounced annual epidemic cycles superimposed on the substantially elevated baseline. Interpretation Bangladesh has experienced an established regime shift to sustained hyperendemic dengue transmission (persistent as of October 2025) necessitating a fundamental shift from outbreak-response to sustained, year-round control strategies. It is most likely influenced by viral, environmental, and societal factors including documented serotype redistribution. Public health strategies must transition from outbreak-response to sustained high-transmission management, including year-round vector control with pre-monsoon intensification.